The atmospheric oxidation of diethyl ether: chemistry of the C2H5-O-CH(O.)CH3 radical between 218 and 335 K - Orlando, John J (Physical chemistry chemical physics : PCCP, 2007)
The products of the Cl atom initiated oxidation of diethyl ether (DEE) were investigated at atmospheric pressure over a range of temperatures (218-335 K) and O(2) partial pressures (50-700 Torr), both in the presence and absence of NO(x). The major products observed at 298 K and below were ethyl formate and ethyl acetate, which accounted for approximately equal to 60-80% of the reacted diethyl ether. In general, the yield of ethyl formate increased with increasing temperature, with decreasing O(2) partial pressure, and upon addition of NO to the reaction mixtures. The product yield data show that thermal decomposition reaction 3, CH(3)CH(2)-O-CH(O.)CH(3)--> CH(3)CH(2)-O-CH=O + CH(3), and reaction 6 with O(2), CH(3)CH(2)-O-CH(O.)CH(3) + O(2)--> CH(3)CH(2)-O-C(=O)CH(3) + HO(2) are competing fates of the CH(3)CH(2)-O-CH(O )CH(3) radical, with a best estimate of k3/k6 approximately equal to 6.9 x 10(24) exp(-3130/T). Thermal decomposition via C-H or C-O bond cleavage are at most minor contributors to the CH(3)CH(2)-O-CH(O.)CH(3) chemistry. The data also show that the CH(3)CH(2)-O-CH(O.)CH(3) radical is subject to a chemical activation effect. When produced from the exothermic reaction of the CH(3)CH(2)-O-CH(OO.)CH(3) radical with NO, prompt decomposition via both CH(3)- and probably H-elimination occur, with yields of about 40% and < or =15%, respectively. Finally, at temperatures slightly above ambient, evidence for a change in mechanism in the absence of NO(x), possibly due to chemistry involving the peroxy radical CH(3)CH(2)-O-CH(OO.)CH(3), is presented.